2021
DOI: 10.3390/insects12040305
|View full text |Cite
|
Sign up to set email alerts
|

Predation on Drosophila suzukii within Hedges in the Agricultural Landscape

Abstract: The invasive Drosophila suzukii feeds and reproduces on various cultivated and wild fruits and moves between agricultural and semi-natural habitats. Hedges in agricultural landscapes play a vital role in the population development of D. suzukii, but also harbor a diverse community of natural enemies. We investigated predation by repeatedly exposing cohorts of D. suzukii pupae between June and October in dry and humid hedges at five different locations in Switzerland. We sampled predator communities and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Maceda-Veiga et al (2021) found a positive association between D. suzukii captures and spatial proximity to streams. Moreover, hedgerow networks are also suspected to foster populations of D. suzukii Siffert et al, 2021). Finally, similarly to other Drosophila species, the dispersal of D. suzukii follows commercial fruit routes (Cini et al, 2014;Lavrinienko et al, 2017) ending in urban areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maceda-Veiga et al (2021) found a positive association between D. suzukii captures and spatial proximity to streams. Moreover, hedgerow networks are also suspected to foster populations of D. suzukii Siffert et al, 2021). Finally, similarly to other Drosophila species, the dispersal of D. suzukii follows commercial fruit routes (Cini et al, 2014;Lavrinienko et al, 2017) ending in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hedgerow networks are also suspected to foster populations of D . suzukii (Santoiemma et al, 2019; Siffert et al, 2021). Finally, similarly to other Drosophila species, the dispersal of D .…”
Section: Introductionmentioning
confidence: 99%